Catch Effectiveness Revealed by Site-Related Differences in Capture–Mark–Recapture Methods: A Butterfly Metapopulation Study. Issue 6 (18th October 2022) - Adamski, Paweł
Abstract: Understanding metapopulation structures is very important in the context of ecological studies and conservation. Crucial in this respect are the abundances of both the whole metapopulation and its constituent subpopulations. In recent decades, capture–mark–recapture studies have been considered the most reliable means of calculating such abundances. In butterfly studies, individual insects are usually caught with an entomological net. But the effectiveness of this method can vary for a number of reasons: differences between fieldworkers, in time, between sites etc. This article analyses catch effectiveness data with respect to two subpopulations of the Apollo butterfly ( Parnassius apollo ) metapopulation in the Pieniny National Park (Polish Carpathians). The results show that this parameter varied significantly between sites, probably because of differences in microrelief and plant cover. In addition, a method is proposed that will include information on catch effectiveness for estimating the sizes of particular subpopulations and will help to elucidate the structure of the entire metapopulation.